THE ROLE OF PARTICULATE MATTER AIR POLLUTION IN CANCER PATHOGENESIS - A. F. Kolpakova; R. N. Sharipov; O. A. Volkova; F. A. Kolpakov (Сибирский онкологический журнал, 2021)
The review highlights contemporary concepts about the role of atmospheric air pollution by particulate matter (pM) in cancer pathogenesis. We used publications from the pubMed and RISC databases. The impact of pMs on the development and progression of cancer was examined with respect to their size, origin, chemical composition and concentration in air. pMs with an aerodynamic diameter of ≤2.5 microns are recognized as the most dangerous. Epidemiological studies revealed a dose-dependent effect of pM on cells. dNA damage and pM-induced epigenetic changes are important components of cancer pathogenesis. Systematized scientific data, especially in the form of formalized descriptions, provide additional insights about concept of cancer pathogenesis and can be used in practical medicine for risk evaluation, early diagnostics, prognosis and increase of the treatment effectiveness.